Exploring the prevalence of chlamydial and gonorrheal infections in pregnant women: a multicenter study in Egypt - Omaima El-Gibaly; Momdouh Wahba; Nahla Gamaleldin; Alaa Hashish; Mostafa Nasr Ibrahim; Ahmed Khedr Khalifa; Sherif Yehia Mohammed; Mohamed Ahmed wasfy; Sara Ali Mohammed Eldosky; Wagdy Amin; Heba Elsayed; Mariam Taher Amin (BMC, 2024)
Abstract Background Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG) are widespread, treatable sexually transmitted infections (STIs) of global significance, affecting millions annually. Left untreated, they pose significant risks, including pelvic inflammatory disease (PID), infertility, and complications during pregnancy. The U.S. Centers for Disease Control recommends annual chlamydial screening for sexually active women to address these risks. Responding to this global challenge, the World Health Organization (WHO) has formulated a global health sector strategy on sexually transmitted infections, outlining priority actions to strengthen STI responses in countries. However, STI epidemiological studies encounter challenges in developing nations like Egypt due to socio-cultural factors, poverty, and limited diagnostic facilities. In Egypt, STI diagnosis primarily relies on clinical presentations, lacking structured screening programs for CT and NG. This study's main objective is to estimate the prevalence of Chlamydial and gonorrheal infections, advocating for supportive STI strategies in Egypt. Additionally, the study aims to provide a foundation for national prevalence estimates of CT and NG infections. Methods A cross-sectional study encompassed five antenatal clinics in different regions of Egypt. A total of 1040 pregnant women attending these clinics were consecutively sampled. Data collection involved structured questionnaires, and urine samples were subjected to the GeneXpert CT/NG qualitative real-time PCR test. Results The prevalence of CT infections was 0.29% (95% CI, 0.10-0.86%), with no detected NG infections. The three CT-positive cases were distributed across different recruitment centers, with no statistically significant differences observed between infected and non-infected participants. Notably, 40.3% of recruited women reported gynecological symptoms, primarily discharge. Additionally, 9.6% had undergone previous testing for sexually transmitted infections, with 8.2% receiving positive results. Conclusions This study provides valuable data on the prevalence of CT and NG infections among pregnant women attending ANC clinics in Egypt. The findings underscore the importance of ongoing surveillance, routine screening, and targeted interventions to ensure the reproductive health and well-being of pregnant women and their infants. Further research is warranted to explore the broader implications of STIs in different populations and to inform evidence-based guidelines for screening and management in diverse settings. Trial registration: IRB no.: 17,400,017; WHO ERC Protocol Id. A66005.